Pengembangan Model Pembelajaran Example Non Example Untuk Meningkatkan Pencapaian Kriteria Ketuntasan Minimal (KKM) - Pipit Herawan; Erliany Syaodih; Bella Anantha Sritumini (EDUCARE, 2012)
The learning process at school is currently not able to develop the potential of students according to their talents, interests and abilities. Even this research is motivated by the condition of students where the achievement of minimum completeness criteria (KKM) of students is still relatively low. This condition greatly affects the low achievement of students in schools, especially in accounting subjects for petty cash funds. The efforts of teachers to carry out accounting learning so far have not been able to reach the determined KKM. Based on these problems, it is necessary to innovate in learning, which aims to find a suitable learning model to increase the achievement of student KKM in accounting subjects. The research method used in this study is research and development (Reserch and Development / R & D), which includes the use of descriptive methods and action research. The implementation of the R & D method is divided into three main steps, namely the preliminary study, the preparation of the model and the trial model. Preliminary studies were carried out on two schools. Limited trials were carried out at SMK Negeri 3 Bandung and extensive trials were conducted at Ma'arif Cicalengka Vocational School.